Adipose stromal cell and sarpogrelate orchestrate the recovery of inflammation‐induced angiogenesis in aged hindlimb ischemic mice. Issue 1 (21st November 2012) - Fan, Weiwei; Li, Chengxiang; Qin, Xing; Wang, Shenxu; Da, Hu; Cheng, Kang; Zhou, Ri; Tong, Chao; Li, Xiujuan; Bu, Qingting; Li, Congye; Han, Yaling; et al.
Summary Aging population displays a much higher risk of peripheral arterial disease (PAD) possibly due to the higher susceptibility, poor prognosis, and fewer therapeutic options. This study was designed to examine the impact of combined multipotent adipose‐derived stromal cells (mADSCs) and sarpogrelate treatment on aging hindlimb ischemia and the mechanism of action involved. mADSCs (1.0 × 107) constitutively expressing enhanced green fluorescent protein (eGFP) or firefly luciferase (Fluc) reporter were engrafted into the hindlimb of aged Vegfr2‐luc transgenic or FVB/N mice subjected to unilateral femoral artery occlusion, followed by a further administration of sarpogrelate. Multimodality molecular imaging was employed to noninvasively evaluate mADSCs' survival and therapeutic efficacy against aging hindlimb ischemia. Aged Tg(Vegfr2‐luc) mice exhibited decreased inflammatory response, and downregulation of vascular endothelial growth factor (VEGF)/vascular endothelial growth factor receptor‐2 (VEGFR2) compared with young ones following hindlimb ischemia induction, resulting in angiogenesis insufficiency and decompensation for ischemia recovery. Engrafted mADSCs augmented inflammation‐induced angiogenesis to yield pro‐angiogenic/anti‐apoptotic effects partly via the VEGF/VEGFR2/mTOR/STAT3 pathway. Nonetheless, mADSCs displayed limited survival and efficacy following transplantation. Sarpogrelate treatment with mADSCs further upregulated mammalian target of rapamycin (mTOR)/STAT3 signal and modulated pro‐/anti‐inflammatory markers including IL‐1β/TNF‐α/IFN‐γ and IL‐6/IL‐10, which ultimately facilitated mADSCs' survival and therapeutic benefit in vivo. Sarpogrelate prevented mADSCs from hypoxia/reoxygenation‐induced cell death via a mTOR/STAT3‐dependent pathway in vitro. This study demonstrated a role of in vivo kinetics of VEGFR2 as a biomarker to evaluate cell‐derived therapeutic angiogenesis in aging. mADSCs and sarpogrelate synergistically restored impaired angiogenesis and inflammation modulatory capacity in aged hindlimb ischemic mice, indicating its therapeutic promise for PAD in the elderly.